Study of the physicochemical and agrochemical properties of the soil of reclaimed areas disturbed by ilmenite mining - Shomko, O. (Scientific Progress & Innovations, 2024)
The article presents the results of research on the physicochemical and agrochemical properties of soil in the reclaimed areas after ilmenite mining. This study investigated the impact of reclamation on the forest vegetation potential of the disturbed soils at different stages, including the 1st year after the start of technical reclamation, 10 th, 20th and 30th years after the start of biological reclamation. Restoration of the ecosystem and forest vegetation potential of the soil using forest reclamation is carried out using a variety of methods, including planting trees, restoring soil composition and stimulating the natural recovery process. The application of these measures can contribute not only to the restoration of vegetation, but also to the preservation of biodiversity and improvement of soil quality in the mining areas. For this reason, the research is aimed at studying the effectiveness of reclamation measures and restoring the forest vegetation potential of the soil. The study location was the operation area affected by the mining activities of the United Mining and Chemical Company (a branch of the Irshansk Mining and Processing Plant) in Zhytomyr region. The following were studied: exchangeable acidity (pHkcl), mobile phosphorus (P2O5), mobile potassium (K2O), easily hydrolyzable nitrogen (NK), exchangeable calcium (Ca) and magnesium (Mg) cations, humus content and the amount of absorbed bases. We analyzed the results and evaluated the changes in those parameters over time and their interaction using statistical analysis. In general, the soil of the research areas has high acidity, low content of humus and low amount of absorbed bases. The content of micro- and macroelements such as phosphorus, potassium, nitrogen, calcium, and magnesium varies from area to area. The conducted research is aimed at studying the effectiveness of reclamation measures to restore the forest vegetation potential of the soil and indicates the need for such research in this sphere. The results obtained can be used to optimize reclamation measures and preserve the stability of soil cover in areas disturbed by mining activities (specifically ilmenite mining) in the future.